SurroundWeb: Mitigating Privacy Concerns in a 3D Web Browser - Vilk, John; Molnar, David; Ofek, Eyal; Rossbach, Chris; Livshits, Ben; Moshchuk, Alexander; Gal, Ran; Wang, Helen (2014)
Immersive experiences that mix digital and real-world objects are becoming reality, but they raise serious privacy concerns as they require real-time sensor input. These experiences are already present on smartphones and game consoles via Kinect, and will eventually emerge on the web platform. However, browsers do not expose the display interfaces needed to render immersive experiences. Previous security research focuses on controlling application access to sensor input alone, and do not deal with display interfaces. Recent research in human computer interactions has explored a variety of high-level rendering interfaces for immersive experiences, but these interfaces reveal sensitive data to the application. Bringing immersive experiences to the web requires a high-level interface that mitigates privacy concerns. This paper presents SurroundWeb, the first 3D web browser, which provides the novel functionality of rendering web content onto a room while tackling many of the inherent privacy challenges. Following the principle of least privilege, we propose three abstractions for immersive rendering:1)the room skeleton lets applications place content in response to the physical dimensions and locations of renderable surfaces in a room; 2) the detection sandbox lets applications declaratively place content near recognized objects in the room without revealing if the object is present; and 3)satellite screens let applications display content across devices registered with SurroundWeb. Through user surveys, we validate that these abstractions limit the amount of revealed information to an acceptable degree.In addition, we show that a wide range of immersive experiences can be implemented with acceptable performance.